Dimethomorph induces heart and vascular developmental defects by disrupting thyroid hormone in zebrafish embryos - You Wei; Yunlong Meng; Kun Jia; Weijian Lu; Yushan Huang; Huiqiang Lu (Ecotoxicology and Environmental Safety)
Dimethomorph (DMT) is a widely-used selective active fungicide that effectively controls downy mildew, crown rot, and late blight in crops. The extensive application of DMT raises concerns about its ecological impact on non-target organisms in the environment. However, there is limited understanding of the toxicological properties of DMT on these organisms. In this study, we utilized zebrafish as an animal model to assess the toxicity of DMT induced by exposure 5.5–72 hours post-fertilization (hpf). During this period, we monitored and evaluated the development of the zebrafish heart and vascular system. Additionally, embryo samples were collected to perform molecular-level detection of PCNA, oxidative stress, and related genes. The results showed a concentration-dependent decrease in survival rate and hatching rate, shortened body length, slowed heart rate, and pericardial edema, body curvature and reduced eye size as DMT exposure concentration increased. Furthermore, DMT exposure led to impairments in the development of the heart, vascular, along with change in the expression levels of relevant genes. It also caused a decrease in cell proliferation and an increase in oxidative stress levels. Moreover, DMT disrupts the normal development of thyroid follicular cells, leading to a reduction in T3 levels. Thyroid hormone supplementation partially reverses the toxicity induced by DMT, increasing eye size, restoring body length, reducing spine curvature, and reducing pericardial edema. Therefore, we speculate that DMT likely affects the development of zebrafish embryos by disrupting normal thyroid follicle development.